40. ASSESSMENT OF RISK FACTORS AFFECTING THE RESULTS OF DECOMPRESSIVE CRANIECTOMY IN PATIENTS WITH BRAIN INJURY (Vietnam Journal of Community Medicine, 2023)
Objectives: To determine the risk factors affecting the results of decompressive craniectomy in patients with traumatic brain injury at Thong Nhat Hospital. Subjects and Methods: A retrospective cross-sectional study of all patients diagnosed with acute subdural hematoma or hemorrhagic cerebral contusion or both with indications for decompressive craniectomy since January 2017 to January 2020 at Thong Nhat Hospital. Results: We collected 172 cases that met the stated conditions and obtained the following results: at the time of discharge, most patients had good outcomes (69.18%), 30, 19% of cases had bad outcomes (GOS 1-2-3). The investigated risk factors affecting the poor outcome included: the amount of newly formed hematoma after surgery >22.68ml (p
Keywords: Decompressive craniotomy, traumatic brain injury (TBI), intraventricular hemorrhage (ICH), hematoma and cerebral contusion, Rotterdam score.